Thucydides and the Politics of Truth - Neville Morley (In Gremium. Studies in History, Culture and Politics, 2021)
Populism, fake news, international rivalries and plague: contemporary events seem to many commentators to echo those described by the ancient Greek historian Thucydides. There is a long tradition of seeing Thucydides as an authority on the present and future as well as the past. This is understood in different ways: historians emphasise the importance of historical knowledge, social scientists see him as a pioneer in normative political theory. His work invites such comparisons, and promises to be 'useful' - not as a source of abstract principles of human behaviour, but as a learning experience, understanding the importance of accurate knowledge about the world and the many ways in which human reasoning can go wrong.